2018
DOI: 10.1016/j.fuel.2018.06.117
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of turbulent flow in a rapid compression machine: Large Eddy Simulation and computationally efficient alternatives for the design of ignition delay time experiments

Abstract: Rapid compression machines (RCMs) are widely used by the fuel research community to provide engine-relevant conditions to study ignition delay time (IDT), which is a crucial target for validating chemical kinetic mechanisms for fuels. Creviced piston heads are routinely used to ensure temperature homogeneity within the combustion chambers of RCMs. However, due to the exponential dependence of kinetic rate coefficients on temperature, homogeneity of the *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For the flow simulations in the RCM, the Reynolds number is estimated around 2000∼4000 in the reaction chamber after EOC, which indicates that the flow pattern resides in the transition region. 7 Yousefian et al 29 compared the 3D large eddy simulation (LES) and 2D laminar results and found that the temperature distributions and velocity fields can be well approximated by 2D laminar simulations, especially at higher pressures. Except for the region in the piston crevice, the flow in the reaction chamber of modern RCMs for chemical kinetic studies is designed to be in laminar condition.…”
Section: Cfd Simulationmentioning
confidence: 99%
“…For the flow simulations in the RCM, the Reynolds number is estimated around 2000∼4000 in the reaction chamber after EOC, which indicates that the flow pattern resides in the transition region. 7 Yousefian et al 29 compared the 3D large eddy simulation (LES) and 2D laminar results and found that the temperature distributions and velocity fields can be well approximated by 2D laminar simulations, especially at higher pressures. Except for the region in the piston crevice, the flow in the reaction chamber of modern RCMs for chemical kinetic studies is designed to be in laminar condition.…”
Section: Cfd Simulationmentioning
confidence: 99%
“…A laminar solver was used since it has been shown to achieve the best agreement with experimental results. 29,31 Furthermore, a laminar CFD model has been proven to adequately predict compression and the postcompression flow field in comparison to the computationally more expensive LES models 4 and the overly dissipative RANS models. 21,22,31 The simulations use the ethanol mechanism by Mittal et al 39 containing 113 species and 710 reactions.…”
Section: Numerical Specificationsmentioning
confidence: 99%
“…Momentum, energy, and species equations were solved considering mixture-averaged diffusion coefficients. A laminar solver was used since it has been shown to achieve the best agreement with experimental results. , Furthermore, a laminar CFD model has been proven to adequately predict compression and the postcompression flow field in comparison to the computationally more expensive LES models and the overly dissipative RANS models. ,, …”
Section: Numerical Specificationsmentioning
confidence: 99%
See 2 more Smart Citations